STUDY OF PROFESSIONAL COMPETENCE IN FUTURE MILITARY SERVANTS IN SOCIAL-PSYCHOLOGICAL RESEARCH (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The article provides scientific information, instructions and recommendations based on statistical, analytical and bibliographic methodology about the factors of formation of professional competence of future military soldiers and the study of this issue in socio-psychological research.